VD_FINDINFO HC / 2012 / 347 vom 7. August 2012 - VD Tribunal cantonal (2012)
ACTION EN MODIFICATION, DIVORCE, DROIT DE GARDE, OBLIGATION D'ENTRETIEN | 134 al. 1 CC, 134 al. 2 CC, 285 al. 1 CC, 285 CC, 286 CC